Kemampuan Memahami Teks Iklan, Slogan, dan Poster Siswa SMP - Fadhlurrohman, Fadhlurrohman; Sukenti, Desi (UIR PRESS, 2023)
The background of this research is that there are still many students who have ability scores below the Minimum Completeness Criteria (KKM) 75 set by the school, so that learning success has not been achieved for 85% of students. The method used in the descriptive method with a quantitative approach. Research data was collected by observation and test techniques. Analysis of research data using descriptive statistics in the form of percentages and categorization. The results showed that: (1) the ability of class VIII students of SMPN 35 Pekanbaru in understanding advertising text material was achieved at an average of 80.86% or in the good category. However, learning mastery was not successful, because it was only achieved in 68.57% of students, or still below the success of 85%; (2) the ability of class VIII students of SMPN 35 Pekanbaru in understanding slogan text material was achieved at an average of 78.00% or in the good category. However, learning mastery was not successful, because it was only achieved in 62.86% of students, or still below the success of 85%; and (3) the ability of class VIII students of SMPN 35 Pekanbaru in understanding the poster text material was achieved at an average of 80.57% or in the good category. However, learning completeness has not been successful, because it is only achieved in 60.00% of students, or is still below the success of 85%.